2017
DOI: 10.18203/2320-6012.ijrms20173703
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of non-alcoholic fatty liver disease in patients of metabolic syndrome in a rural population attending tertiary care centre

Abstract: Background: Non-alcoholic fatty liver disease and steatohepatitis now constitute the major etiology of chronic liver disease. Prevalence of non-alcoholic fatty liver disease is rising due to the change in lifestyle habits, diet and obesity. Metabolic syndrome is closely related with the pathogenesis of non-alcoholic fatty liver disease. Studies showed that prevalence of metabolic syndrome is rising in Indian population. This study was conducted to look into the current status of the metabolic syndrome in rural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…A total of 15 articles made it to the final review [ 29 - 43 ]. Table 3 contains the details of the relevant 15 articles included [ 29 - 43 ].…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 15 articles made it to the final review [ 29 - 43 ]. Table 3 contains the details of the relevant 15 articles included [ 29 - 43 ].…”
Section: Reviewmentioning
confidence: 99%
“…In studies that find the association between NAFLD and MetS, the prevalence of NAFLD in MetS is found to be higher (91.4%) [ 29 , 31 , 32 , 37 , 39 , 43 , 40 ]. The above-mentioned studies have found a statistically significant association between NAFLD and MetS in study participants from India, Iran, Malaysia, Nepal, and China.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations